Positive electrode active material and method of manufacture, positive electrode, lithium ion battery

CN117239100BActive Publication Date: 2026-10-30TIANJIN B&M SCI & TECH LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311463219.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-06
Publication Date
2026-10-30
Estimated Expiration
2043-11-06

AI Technical Summary

Technical Problem

然而,传统金属氧化物包覆的材料的表层依然存在金属溶出以及材料表面结构稳定性差的缺点,且对材料电化学性能的改善有限

Benefits of technology

[0036]本申请提供的正极活性材料通过在锂过渡金属氧化物粒子表面包覆锚定层,平均化合价较低的硫元素能够与锂过渡金属氧化物粒子中的活性元素(过渡金属、B等)以化学键连接,进而能够有效稳定正极活性材料表面的金属活性位点,并能够削弱表面活性过渡金属元素与电解液反应而导致的表面过渡金属溶出,从而改善了正极活性材料界面的结构稳定性。同时,层叠在所述锚定层上的稳定层中,硫元素的平均化合物相对于锚定层较高,能够对锚定层起到保护作用,使稳定层具备较高的电化学活性,能够有效抑制材料的极化,协同锚定层能够使本申请提供的正极活性材料兼备较高的离子电导性和电子电导性,能显著提高正极活性材料的电化学性能,包括高容量、低内阻和高循环稳定性等。进一步地,本申请提供的正极活性材料易于制备,可实现规模化生产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117239100B_ABST
    Figure CN117239100B_ABST
Patent Text Reader

Abstract

The application relates to a positive electrode active material and a preparation method, a positive electrode, a lithium ion battery and a power utilization device. The positive electrode active material provided by the application is coated with an anchoring layer on the surface of a substrate, the sulfur element with a relatively low average valence can be connected to active elements (transition metals, B, etc.) in lithium transition metal oxide particles through a chemical bond, thereby effectively stabilizing the metal active sites on the surface of the positive electrode active material, and weakening the surface transition metal dissolution caused by the reaction between the surface active transition metal elements and the electrolyte. Meanwhile, the stabilizing layer stacked on the anchoring layer can protect the anchoring layer, and the stabilizing layer has relatively high electrochemical activity, can effectively inhibit the polarization of the material, and can make the positive electrode active material provided by the application have relatively high ionic conductivity and electronic conductivity, thereby significantly improving the electrochemical performance of the positive electrode active material, including high capacity, low internal resistance and high cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of cathode material technology, specifically to a cathode active material and its preparation method, a cathode, and a lithium-ion battery. Background Technology

[0002] Because lithium-ion batteries have advantages such as high operating voltage, light weight, small size, low self-discharge rate, long cycle life and high energy density, they are now widely used in mobile terminal products such as mobile phones, laptops and tablets.

[0003] However, lithium-ion cathode materials suffer from surface structural changes under high-voltage and high-temperature charge-discharge conditions, leading to significant performance degradation. To improve surface stability, metal oxide coating methods are commonly used, employing inert nano-inorganic oxides such as aluminum oxide, magnesium oxide, titanium oxide, and zinc oxide for solid-state coating. However, traditional metal oxide-coated materials still suffer from drawbacks such as metal leaching and poor surface structural stability, and offer limited improvement to electrochemical performance. Summary of the Invention

[0004] Based on this, this application provides a positive electrode active material, a preparation method, a positive electrode, and a lithium-ion battery. The positive electrode active material provided by this application can effectively reduce metal dissolution and improve the structural stability of the material, thereby effectively improving the electrochemical performance of the material.

[0005] In a first aspect, this application provides a positive electrode active material, comprising lithium transition metal oxide particles and a coating layer disposed on the surface of the lithium transition metal oxide particles, the coating layer comprising an anchoring layer and a stabilizing layer stacked thereon, wherein the anchoring layer is closer to the surface of the lithium transition metal oxide particles than the stabilizing layer.

[0006] The anchoring layer and the stabilizing layer include sulfur, and the average valence of the sulfur in the stabilizing layer is greater than the average valence of the sulfur in the anchoring layer.

[0007] The anchoring layer is used to anchor the active elements in the lithium transition metal oxide particles, and the total dissolution amount of transition metal in the lithium transition metal oxide particles with the coating layer is ≤4000ppm.

[0008] In one embodiment, the lithium transition metal oxide particles have the chemical formula Li. 1+x Ni y R z M 1-y-z O uWherein, -0.2≤x≤0.2, 0.3≤y≤0.8, 0≤z≤0.7, y+z≤1, 1.8≤u≤2.2; R includes one or more of Co or Mn; M includes one or more of Al, Zr, Mg, Ti, W, B, Y, Sr, Nb and Mo.

[0009] In one example, the anchoring layer is formed by inducing Ni, R, or M in the lithium transition metal oxide particles through sulfide Q2S, where Q includes Na. + Li + and NH4 + One or more of the following; the anchoring layer satisfies m1=-2; where m1 is the average valence of sulfur contained in the anchoring layer;

[0010] The stabilizing layer is formed by inducing the formation of the sulfide Q2S through elemental sulfur, such that the oxidation state of the sulfur element contained in the stabilizing layer satisfies -2 < m < 0. The stabilizing layer also satisfies -2 < m2 < 0, where m2 is the average oxidation state of the sulfur element contained in the stabilizing layer.

[0011] In one embodiment, the lithium transition metal oxide particles have a particle size of 2 μm to 15 μm.

[0012] In one embodiment, the thickness of the anchoring layer is 5nm to 50nm.

[0013] In one embodiment, the thickness of the stabilizing layer is 5nm to 50nm.

[0014] In one embodiment, after the positive electrode active material is assembled into a coin cell and cycled 50 times, the ratio of the 003 peak to the 104 peak in the X-ray diffraction refinement test of the positive electrode active material is ≥1.45.

[0015] In one embodiment, after the positive electrode active material is assembled into a coin cell and cycled 50 times, the change rate of the interlayer distance ΔH between the transition metal and oxygen in the positive electrode active material is ≤10% in the X-ray diffraction refinement test; where ΔH=(H2-H1) / H1, H2 represents the interlayer distance between the transition metal and oxygen in the positive electrode active material after 50 cycles; H1 represents the interlayer distance between the transition metal and oxygen in the positive electrode active material at 0 cycles.

[0016] A second aspect of this application provides a method for preparing a positive electrode active material, comprising the following steps:

[0017] The lithium transition metal oxide particles and sulfide Q2S were mixed and calcined at a temperature of 200℃~700℃ to prepare a sulfide Q2S pre-coated lithium transition metal oxide modified material; Q includes Na.+ Li + and NH4 + One or more of the following;

[0018] Sol A is prepared by mixing the sulfide Q2S pre-coated lithium transition metal oxide modified material and dispersant in carbon disulfide solvent;

[0019] Solution B is prepared by dissolving elemental sulfur in carbon disulfide solvent;

[0020] The solution B is introduced into sol A for deposition, and after solid-liquid separation, it is sintered at a temperature of 200℃~800℃ to prepare the positive electrode active material.

[0021] In one embodiment, the mass ratio of the lithium transition metal oxide particles to sulfide Q2S is 1:(0.001~0.1).

[0022] In one embodiment, the solid content of sol A is 5% to 50%.

[0023] In one embodiment, the concentration of sulfur in solution B is 0.001 mol / L to 0.1 mol / L.

[0024] In one embodiment, the introduction rate of solution B into sol A is 0.4 g / min to 0.6 g / min.

[0025] In one embodiment, the mass ratio of the sulfide-coated lithium transition metal oxide modified material to the elemental sulfur is 1:(0.001~0.1).

[0026] In one embodiment, the dispersant comprises one or more of dodecyltrimethylammonium chloride, dodecyltrimethylammonium bromide, and octadecyldimethylbenzylammonium chloride.

[0027] In one embodiment, the preparation steps of the lithium transition metal oxide particles include:

[0028] A mixture is prepared by mixing the precursor with a lithium source;

[0029] The mixture was sintered at a temperature of 400℃~1000℃ to prepare the lithium transition metal oxide particles;

[0030] The precursor has the chemical formula Ni y1 R z1 M 1-y1-z1 O u1Wherein, 0.3≤y1≤0.8, 0≤z1≤0.7, y1+z1≤1, 1.8≤u1≤2.2; R includes one or more of Co or Mn; M includes one or more of Al, Zr, Mg, Ti, W, B, Y, Sr, Nb and Mo.

[0031] A third aspect of this application provides a positive electrode, comprising a positive electrode current collector and a positive electrode active material layer stacked on the surface of the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode active material described in any embodiment of the first aspect of this application or the positive electrode active material prepared by the preparation method described in any embodiment of the second aspect of this application.

[0032] A fourth aspect of this application provides a lithium-ion battery, comprising:

[0033] The positive electrode described in the third aspect of this application;

[0034] The negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector;

[0035] Diaphragm and electrolyte.

[0036] The positive electrode active material provided in this application utilizes an anchoring layer coated on the surface of lithium transition metal oxide particles. Sulfur, with its relatively low average valence, can chemically bond with active elements (transition metals, B, etc.) within the lithium transition metal oxide particles, effectively stabilizing the metal active sites on the surface of the positive electrode active material. This also reduces the dissolution of surface transition metals caused by the reaction between surface-active transition metal elements and the electrolyte, thereby improving the structural stability of the positive electrode active material interface. Simultaneously, in the stabilizing layer layer stacked on the anchoring layer, the average sulfur compound content is relatively high compared to the anchoring layer, providing protection for the anchoring layer and giving it high electrochemical activity. This effectively suppresses material polarization, and the synergistic effect of the anchoring layer enables the positive electrode active material provided in this application to possess both high ionic and electronic conductivity, significantly improving its electrochemical performance, including high capacity, low internal resistance, and high cycle stability. Furthermore, the positive electrode active material provided in this application is easy to prepare and can be mass-produced. Attached Figure Description

[0037] Figure 1 The diagram shows the structure of the positive electrode active material provided in this application, wherein 10 is a lithium transition metal oxide particle, 20 is an anchoring layer, and 30 is a stabilizing layer.

[0038] Figure 2 These are XRD comparison images of the positive electrode active materials prepared in Examples 1-2 and Comparative Examples 1-2 of this application;

[0039] Figure 3This is a comparison diagram of the dissolution of Ni and Co elements in the electrolyte of the positive electrode active materials prepared in Examples 1-3 and Comparative Examples 1-4 of this application at 60°C.

[0040] Figure 4 This is a comparison chart of the rate performance of the positive electrode active materials prepared in Examples 1-3 and Comparative Examples 1-4 of this application at 25°C. Detailed Implementation

[0041] The following detailed description, in conjunction with specific embodiments, provides a more complete and clear account of the positive electrode active material, its preparation method, the positive electrode, the lithium-ion battery, and the power application device of this application. This application can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the disclosure of this application.

[0042] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application.

[0043] In this article, "one or more" refers to any one, two or more of the listed items.

[0044] In this application, terms such as "first aspect," "second aspect," "third aspect," "fourth aspect," and "fifth aspect" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be construed as implicitly indicating the importance or quantity of the indicated technical features. Moreover, terms such as "first," "second," "third," "fourth," and "fifth" serve only as a non-exhaustive enumeration and should be understood not to constitute a closed limitation on quantity.

[0045] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.

[0046] In this application, numerical ranges are referred to as continuous unless otherwise specified, and include the minimum and maximum values ​​of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values ​​of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.

[0047] Unless otherwise specified, the percentage content mentioned in this application refers to mass percentage for solid-liquid mixtures and solid-phase-solid mixtures, and volume percentage for liquid-phase-liquid mixtures.

[0048] Unless otherwise specified, all percentage concentrations mentioned in this application refer to the final concentration. The final concentration refers to the proportion of the added component in the system after the addition of that component.

[0049] Unless otherwise specified, the temperature parameters in this application may be either constant temperature processing or processing within a certain temperature range. The constant temperature processing allows for temperature fluctuations within the precision range controlled by the instrument.

[0050] Based on extensive experience and research, the inventors of this application have discovered that lithium-ion cathode materials exhibit structural changes on their surface under high voltage or charge / discharge conditions, leading to battery performance degradation. One reason for this is that, during high-voltage and high-temperature charge / discharge, the highly active transition metal sites on the surface of the cathode active material react with the electrolyte to form HF acid, a byproduct that causes the dissolution of active transition metal elements from the material surface. Another reason is the excessive activity of the surface transition metal elements. Traditional solid-phase oxide coating methods, using oxides such as aluminum oxide, magnesium oxide, titanium oxide, and zinc oxide, only physically coat the substrate surface and cannot effectively passivate the active sites of the transition metal elements, thus failing to stabilize the surface transition metal elements.

[0051] Based on this, in a first aspect, a positive electrode active material is provided, comprising lithium transition metal oxide particles and a coating layer disposed on the surface of the lithium transition metal oxide particles, wherein the coating layer comprises an anchoring layer and a stabilizing layer stacked thereon, and the anchoring layer is closer to the surface of the lithium transition metal oxide particles than the stabilizing layer.

[0052] The anchoring layer and the stabilizing layer include sulfur, and the average valence of the sulfur in the stabilizing layer is greater than the average valence of the sulfur in the anchoring layer.

[0053] The anchoring layer is used to anchor the active elements in the lithium transition metal oxide particles, and the total dissolution amount of transition metal in the lithium transition metal oxide particles with the coating layer is ≤4000ppm.

[0054] The cathode active material provided in this application stabilizes the transition metal active sites on the surface of lithium transition metal oxide particles by inducing the formation of an anchoring layer on the surface of lithium transition metal oxide particles, where active elements and sulfur elements with relatively low average valence are chemically bonded. This results in a total transition metal dissolution rate of ≤4000 ppm in the cathode active material provided in this application. Simultaneously, the sulfur element in the outermost stabilizing layer has a higher valence than that in the anchoring layer; thus, the stabilizing layer exhibits higher electrochemical activity, enabling the cathode active material to possess both high ionic and electronic conductivity, and improving its electrochemical performance, including high capacity, low internal resistance, and high cycle stability.

[0055] In one example, the lithium transition metal oxide particles have the chemical formula Li. 1+x Ni y R z M 1-y-z O u Where -0.2≤x≤0.2, 0.3≤y≤0.8, 0≤z≤0.7, y+z≤1, 1.8≤u≤2.2; R includes one or more of Co or Mn; M includes one or more of Al, Zr, Mg, Ti, W, B, Y, Sr, Nb, and Mo. The values ​​of x, y, z, and u may vary depending on the ratio between the elements, but are all set within the range that allows the compound represented by the chemical formula to be used as a lithium transition metal oxide particle. Specifically, when R is Co, the chemical formula of the lithium transition metal oxide particle includes, but is not limited to, Li. 1+ x Ni y Co z Al 1-y-z Ternary materials such as O2. When R is Mn, the chemical formula of lithium transition metal oxide particles includes, but is not limited to, LiNi. 0.5 Mn 0.5 O2, LiNi 0.9 Mn 0.1 Binary materials such as O2. When R is Co and Mn, the chemical formulas of lithium transition metal oxide particles include, but are not limited to, LiNi. 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.6 Co 0.1 Mn 0.3 O2, LiNi 0.63 Co 0.08 Mn 0.29 O2, LiNi 0.63 Co 0.05 M n0.32O2, LiNi 0.65 Co 0.07 Mn 0.28 O2, LiNi 0.7 Co 0.1 Mn 0.3 O2, LiNi 0.72 Co 0.05 Mn 0.23 O2, LiNi 0.68 Co 0.08 Mn 0.24 O2, LiNi 0.83 Co 0.12 Mn 0.05 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2、;LiNi a Co b Mn c Al d Quaternary materials such as O2 (a+b+c+d=1).

[0056] In one example, the anchoring layer is formed by inducing the formation of active elements in the lithium transition metal oxide particles through sulfide Q2S, where Q includes Na. + Li + and NH4 + One or more of the following. The anchoring layer satisfies m1=-2; where m1 is the average valence of sulfur contained in the anchoring layer.

[0057] In this application, the anchoring layer is formed through interface-induced formation of a lithium transition metal oxide modified material pre-coated with sulfide Q2S. The sulfide Q2S anchors the active elements at the interface of the lithium transition metal oxide particles, allowing the sulfur element to chemically bond with the active elements in the lithium transition metal oxide particles. This reduces the dissolution of transition metals in the positive electrode active material of this application, ensuring a total dissolution of transition metals ≤4000ppm. In one example, the lithium transition metal oxide particles include one or more of the active elements Ni, Co, Mn, Al, Zr, Mg, Ti, W, Y, Sr, Nb, and Mo. Under appropriate conditions, the active elements at the interface can bond with S... 2-Stable nickel sulfide, cobalt sulfide, manganese sulfide, aluminum sulfide, zirconium sulfide, magnesium sulfide, titanium sulfide, tungsten sulfide, boron sulfide, yttrium sulfide, strontium sulfide, niobium sulfide, and molybdenum sulfide are formed. Therefore, it can be understood that the anchoring layer includes one or more of nickel sulfide, cobalt sulfide, manganese sulfide, aluminum sulfide, zirconium sulfide, magnesium sulfide, titanium sulfide, tungsten sulfide, boron sulfide, yttrium sulfide, strontium sulfide, niobium sulfide, and molybdenum sulfide. In one example, the interface-induced conditions for the Q2S sulfide pre-coated lithium transition metal oxide modified material include a sintering temperature of 200°C to 800°C.

[0058] In one example, the stabilizing layer is formed by inducing the formation of sulfide Q2S with elemental sulfur, such that the stabilizing layer satisfies: -2 < m2 < 0; where m2 is the average valence of sulfur contained in the stabilizing layer. In this application, the stabilizing layer is formed by inducing the formation of an interface between elemental sulfur and sulfide Q2S pre-coated lithium transition metal oxide modified material. Sulfide Q2S provides S 2- Under the induction of elemental sulfur in the outermost layer, the valence m of sulfur in the outermost stable layer satisfies -2 < m < 0. This results in high electrochemical activity in the stable layer, and the sulfur with a valence greater than -2 further stabilizes the active elements, increasing the average valence of the active elements in the cathode active material provided in this application. Furthermore, taking the lithium transition metal oxide particles containing transition metal Ni as an example, the sulfur with a valence greater than -2 in the stable layer has a stabilizing effect on the active sites of Ni, increasing the average valence of Ni (>2.3), thereby inhibiting the formation of surface rock salt phases such as divalent nickel compounds NiO, thus ensuring the electrochemical performance of the cathode active material provided in this application. The conditions for the interface induction between the sulfide Q2S pre-coated lithium transition metal oxide modified material and elemental sulfur include a sintering temperature of 200℃~800℃.

[0059] Furthermore, it is understood that in the chemical formula of the aforementioned lithium transition metal oxide particles, the value of y is 0.3 ≤ y ≤ 0.8, meaning that the proportion of Ni element in the lithium transition metal oxide particles based on the sum of the molar numbers of Ni, R, and M is ≥ 30%. Thus, the lithium transition metal oxide particles have sufficient active cation sites, and the S in sulfide Q2S... 2- The active cations in the lithium transition metal oxide particles are attracted to each other through electrostatic interactions, which induces them to connect through chemical bonds, thereby ensuring the stabilizing effect of the anchoring layer on the active sites.

[0060] Furthermore, to avoid the self-formation of sulfides in the lithium transition metal oxide particles, which would reduce the cycle life of the battery, in one example, the molar fraction of sulfur in the lithium transition metal oxide particles is ≤1000 ppm.

[0061] The particle size of lithium transition metal oxide (LiMO) particles has a significant impact on the energy density of the battery cell and the compaction density of the electrode. A slightly smaller particle size in the matrix results in a slightly lower energy density of the battery cell; conversely, a slightly larger particle size results in a slightly lower compaction density of the electrode. To balance the energy density and compaction density of the LiMO particles, in one example, the particle size of the LiMO particles is 2 μm to 15 μm. Understandably, the particle size of the LiMO particles can be selected from any value between 2 μm and 15 μm. Specifically, the particle size of the LiMO particles includes, but is not limited to, 2 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, or 15 μm. In this application, unless otherwise specified, the terms "size," "particle size," and "diameter" generally refer to average values. In this application, "particle size" represents the average particle size of spheres or quasi-spheres.

[0062] In one example, the thickness of the anchoring layer is 5 nm to 50 nm. It is understood that the thickness of the anchoring layer can be selected from any value between 5 nm and 50 nm. Specifically, the thickness of the anchoring layer includes, but is not limited to, 5 nm, 10 nm, 15 nm, 20 nm, 30 nm, 40 nm, or 50 nm.

[0063] In one example, the thickness of the stabilizing layer is 5 nm to 50 nm. Understandably, the thickness of the stabilizing layer can be selected from any value between 5 nm and 50 nm. Specifically, the thickness of the stabilizing layer includes, but is not limited to, 5 nm, 10 nm, 15 nm, 20 nm, 30 nm, 40 nm, or 50 nm.

[0064] This application sets the thickness of the anchoring layer and the stabilizing layer within this range, which is beneficial to achieving the best electrochemical performance of the positive electrode active material. It avoids the inability to isolate the electrode / electrolyte interface reaction caused by the anchoring layer and the stabilizing layer being too thin, and also avoids the instability of the phase interface caused by their being too thick.

[0065] In one example, the mass ratio of the coating layer to the lithium transition metal oxide particles is 1:(100~1000). At this ratio, the masses of the coating layer and the lithium transition metal oxide particles are well-matched, making it easy to adjust the thickness of the coating layer and enabling the positive electrode active material to effectively suppress the dissolution of active transition metals. When the positive electrode active material prepared in this application is assembled into a coin cell and stored at 4.45V@SOC100 for 30 days at 60°C, the total dissolution of active transition metal elements such as Ni, Co, Mn, Al, Zr, Mg, Ti, W, B, Y, Sr, Nb, and Mo is no higher than 4000 ppm; furthermore, it can improve electronic conductivity, lithium-ion conductivity, and interface stability. Specifically, the mass ratio of the coating layer to the lithium transition metal oxide particles includes, but is not limited to, 1:100, 1:200, 1:300, 1:400, 1:500, 1:600, 1:700, 1:800, 1:900, or 1:1000.

[0066] A second aspect of this application provides a method for preparing the positive electrode active material described in any example of the first aspect of this application, comprising the following steps:

[0067] S3. The lithium transition metal oxide particles and sulfide Q2S are mixed and calcined at a temperature of 200℃~700℃ to prepare a sulfide Q2S pre-coated lithium transition metal oxide modified material; Q includes Na. + Li + and NH4 + One or more of the following;

[0068] S4. The sulfide Q2S pre-coated lithium transition metal oxide modified material and dispersant are mixed in carbon disulfide solvent to prepare sol A;

[0069] S5. Dissolve elemental sulfur in carbon disulfide solvent to prepare solution B;

[0070] S6. The solution B is introduced into sol A for deposition. After solid-liquid separation, it is sintered at a temperature of 200℃~800℃ to form an anchoring layer and a stabilizing layer, thereby preparing the positive electrode active material.

[0071] In one example, in step S3, the mass ratio of the lithium transition metal oxide particles to sulfide Q2S is 1:(0.001~0.1). By limiting the mass ratio of lithium transition metal oxide particles to sulfide Q2S, the lithium transition metal oxide particles and sulfide Q2S are easily dispersed, and the dispersion time can be effectively shortened. Further, the mass ratio of lithium transition metal oxide particles to sulfide Q2S includes, but is not limited to, 1:0.001, 1:0.005, or 1:0.1.

[0072] In one example, the process parameters for mixing the lithium transition metal oxide particles and sulfide Q2S in step S3 include: mixing time ≥ 24h.

[0073] In addition, it is understood that the apparatus for mixing lithium transition metal oxide particles and sulfide Q2S in step S3 is not limited in this application, and the apparatus for mixing can be exemplified by a microwave ultrasonic instrument.

[0074] In one example, in step S3, the calcination process parameters include: a calcination temperature of 200℃~700℃ and a calcination time of 6h~24h. Specifically, the calcination temperature includes, but is not limited to, 200℃, 250℃, 300℃, 350℃, 400℃, 450℃, 500℃, 600℃, or 700℃. The calcination time includes, but is not limited to, 6h, 7h, 8h, 10h, 12h, 15h, 18h, 20h, 22h, or 24h.

[0075] In one example, the mass ratio of the Q2S sulfide pre-coated lithium transition metal oxide modifier to sulfur is 1:(0.001~0.1). Specifically, the mass ratio of the Q2S sulfide pre-coated lithium transition metal oxide modifier to sulfur is, but is not limited to, 1:0.001, 1:0.005, or 1:0.1:0.1. Limiting the mass ratio of the Q2S sulfide pre-coated lithium transition metal oxide modifier to sulfur allows the outermost sulfide to react with the sulfur, facilitating a more complete reaction.

[0076] In one example, in step S4, the dispersant includes one or more of dodecyltrimethylammonium chloride, dodecyltrimethylammonium bromide, and octadecyldimethylbenzylammonium chloride.

[0077] In one example, in step S4, the solid content of sol A is 5% to 50%. The solid content of sol A includes, but is not limited to, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, or 50%.

[0078] In one example, in step S5, the concentration of elemental sulfur in solution B is 0.001 mol / L to 0.001 mol / L. The concentration of elemental sulfur in solution B includes, but is not limited to, 0.001 mol / L, 0.002 mol / L, 0.005 mol / L, 0.008 mol / L, 0.01 mol / L, 0.02 mol / L, 0.05 mol / L, 0.07 mol / L, 0.09 mol / L, 0.1 mol / L, 0.5 mol / L, 0.8 mol / L, or 1 mol / L. Preferably, the elemental sulfur is sulfur.

[0079] In one example, in step S6, the introduction rate of solution B into sol A is 0.4 g / min to 0.6 g / min. Specifically, the introduction rate includes, but is not limited to, 0.4 g / min, 0.45 g / min, 0.5 g / min, 0.55 g / min, or 0.6 g / min. Understandably, on the one hand, step S6 can induce an interfacial reaction in the sulfide Q2S pre-coated lithium transition metal oxide modified material, causing the sulfur element therein to connect with the active element in the lithium transition metal oxide particles through chemical bonds, thereby anchoring the active element at the lithium transition metal oxide particle interface; on the other hand, the sulfide Q2S pre-coated lithium transition metal oxide modified material reacts with elemental sulfur to generate the stable layer of this application, such that the average valence of sulfur element in the stable layer is between -2 and 0, thus successfully preparing the positive electrode active material of this application. In this application, the device for introducing solution B into sol A includes, but is not limited to, a peristaltic pump.

[0080] By limiting the solid content of sol A, the sulfur concentration of solution B, and the introduction rate of solution B into sol A, the thickness and coating rate of the coating layer can be effectively controlled, thereby driving the prepared coating layer to form a stable layer on the surface.

[0081] In one example, the sintering process parameters for step S6 include: a sintering temperature of 200℃~800℃ and a sintering time of 8h~30h. Specifically, the sintering temperature includes, but is not limited to, 200℃, 250℃, 300℃, 350℃, 400℃, 450℃, 500℃, 600℃, 700℃, 750℃, or 800℃. The sintering time includes, but is not limited to, 8h, 9h, 12h, 15h, 20h, 25h, or 30h. By limiting the sintering temperature and sintering time, on the one hand, the active elements at the lithium transition metal oxide particle-sulfide Q2S interface can be made more readily reacted with S. 2- Anchoring is performed to stabilize the active transition metal elements on the surface; on the other hand, it enables the sulfide Q2S to react with elemental sulfur, so that the average oxidation state of sulfur in the stable layer is between -2 and 0.

[0082] In one example, the preparation steps of the lithium transition metal oxide particles include:

[0083] S1. Mix the precursor with a lithium source to prepare a mixture;

[0084] S2. The mixture is sintered at a temperature of 400℃~1000℃ to prepare the lithium transition metal oxide particles.

[0085] In one example, in step S1, the precursor has the chemical formula Ni. y1 Rz1 M 1-y1-z1 O u1 Wherein, 0.3≤y1≤0.8, 0≤z1≤0.7, y1+z1≤1, 1.8≤u1≤2.2; R includes one or more of Co or Mn; M includes one or more of Al, Zr, Mg, Ti, W, B, Y, Sr, Nb, and Mo. Specifically, when R is Co, the chemical formula of the precursor includes, but is not limited to, Ni. y Co z Al 1-y-z (OH)₂, etc. When R is Mn, the chemical formula of the precursor includes, but is not limited to, Ni. 0.5 Mn 0.5 (OH)2, Ni 0.9 Mn 0.1 (OH)₂, etc. When R is Co and Mn, the chemical formula of the precursor includes, but is not limited to, Ni. 1 / 3 Co 1 / 3 Mn 1 / 3 (OH)2, Ni 0.5 Co 0.2 Mn 0.3 (OH)2, Ni 0.6 Co 0.1 Mn 0.3 (OH)2, Ni 0.63 Co 0.08 Mn 0.29 (OH)2, Ni 0.63 Co 0.05 M n0.32 (OH)2, Ni 0.65 Co 0.07 Mn 0.28 (OH)2, Ni 0.7 Co 0.1 Mn 0.3 (OH)2, Ni 0.72 Co 0.05 Mn 0.23 (OH)2, Ni 0.68 Co 0.08 Mn 0.24 (OH)2, Ni 0.83 Co 0.12 Mn 0.05 (OH)2, Ni 0.8 Co 0.1 Mn 0.1 (OH)2、、Ni a Co b Mn c Al d (OH)2 (a+b+c+d=1).

[0086] In one example, in the mixture of step S1, the molar number of lithium elements in the lithium source is related to the molar number of the precursor Ni. y1 R z1 M 1-y1-z1 O u1 The ratio of the total molar number of metallic elements in the lithium source to the total molar number of the precursor Ni is 0.8~1.2:1. Specifically, the ratio of the molar number of lithium elements in the lithium source to the total molar number of Ni precursor Ni is 0.8~1.2:1. y1 R z1 M 1-y1-z1 O u1 The ratio of the total number of moles of metallic elements in a medium is including but not limited to 1.2:1, 1.1:1, 1:1, 0.9:1 or 0.8:1.

[0087] In one example, in step S1, the lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium acetate, lithium citrate, and lithium oxalate.

[0088] In one example, in step S2, the sintering process parameters include: a sintering temperature of 400℃~1000℃ and a sintering time of 8h~30h. Specifically, the sintering temperature includes, but is not limited to, 400℃, 500℃, 600℃, 700℃, 800℃, 900℃, or 1000℃. The sintering time includes, but is not limited to, 8h, 10h, 12h, 15h, 18h, 20h, 25h, or 30h.

[0089] In one example, the sintering in step S2 is carried out in an atmosphere of oxygen and / or air.

[0090] A third aspect of this application provides a positive electrode for a lithium-ion battery, comprising a positive electrode current collector and a positive electrode active material layer stacked on the surface of the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode active material described in any one of the first aspects of this application or the positive electrode active material prepared by the preparation method described in any one of the examples of the second aspect of this application.

[0091] A fourth aspect of this application provides a lithium-ion battery, comprising:

[0092] The positive electrode of the lithium-ion battery described in the third aspect of this application;

[0093] The negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector;

[0094] Diaphragm and electrolyte.

[0095] The negative electrode, separator, and electrolyte can be made of conventional negative electrode current collector, separator, and electrolyte materials in the art, and the present invention does not impose any particular limitations on them.

[0096] The negative electrode current collector can be copper, and its shape is not particularly limited; it can be rod-shaped, plate-shaped, sheet-shaped, or foil-shaped, depending on the shape of the lithium-ion battery. The negative electrode active material layer includes a negative electrode active material, conductive additives, and a binder. The negative electrode active material, conductive additives, and binder are also conventional materials in the art. In some embodiments, the negative electrode active material is metallic lithium.

[0097] The separator can be selected from separators commonly used in lithium-ion batteries, such as polyolefin films, including microporous membranes made of polyethylene and polypropylene; multilayer membranes of porous polyethylene and polypropylene; nonwoven fabrics formed of polyester fibers, aramid fibers, glass fibers, etc.; and base membranes formed by attaching ceramic particles such as silica, alumina, and titanium dioxide to their surfaces. In some embodiments, the separator is a three-layer membrane of PP / PE / PP coated with alumina on both sides.

[0098] The electrolyte may include an electrolyte and a non-aqueous organic solvent. The electrolyte is preferably LiPF6, LiBF4, LiSbF6, or LiAsF6. The non-aqueous organic solvent may be a carbonate, ester, or ether. Carbonates, such as ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC), are preferred. In some embodiments, the electrolyte is a non-aqueous electrolyte of ethylene carbonate (EC) / dimethyl carbonate (DMC) with a LiPF6 concentration of 1 mol / L, wherein the volume ratio of EC to DMC is 1:1.

[0099] This application also provides an electrical device including the lithium-ion battery described in the fourth aspect of this application.

[0100] The following are specific embodiments, intended to provide a more detailed description of the present invention to help those skilled in the art and researchers to further understand it. The technical conditions described do not constitute any limitation on the present invention. Any modifications made within the scope of the claims of this invention are protected within the scope of the claims.

[0101] Example 1

[0102] (1) Preparation of lithium transition metal oxide particles

[0103] The precursor material (Ni) 0.6 Co 0.4(OH)₂ (purchased from Aladdin Reagent, particle size 2~15μm) was mixed with lithium hydroxide to prepare a mixture, in which the molar ratio of Li to (Ni+Co) in the mixture was 1.05:1; the mixture was heated in a box furnace under oxygen atmosphere at 950℃ for 15 h, and then pulverized by rollers (upper gap 15cm, lower gap 5cm) to obtain LiN i0.6 Co 0.4 O2 matrix.

[0104] (2) Preparation of sulfide Li2S pre-coated lithium transition metal oxide modified materials

[0105] Take the LiN prepared in step (1) i0.6 Co 0.4 2500g of O2 matrix was mixed with 10.5g of lithium sulfide using a solid-state method at 1200 rpm / min, and then calcined at 400℃ for 8h to prepare sulfide Li2S pre-coated lithium transition metal oxide modified material.

[0106] (3) Preparation of positive electrode active material

[0107] Take 100g of the sulfide Li2S pre-coated lithium transition metal oxide modified material prepared in step (2), add 5g of dodecyltrimethylammonium chloride to 200g of carbon disulfide solution, and stir at 300rpm / min until a stable sol A with a solid content of 48.8% is formed.

[0108] Add 5g of sulfur to 200g of carbon disulfide and stir at 500rpm / min to dissolve, thus preparing a solution B with a sulfur concentration of 0.98mol / L.

[0109] Solution B was introduced into sol A at a rate of 0.5 g / min using a peristaltic pump. After the addition was complete, stirring was continued for 24 h. After solid-liquid separation, the solid was collected. The solid was then calcined at 300 °C for 6 h under an Ar atmosphere to induce the formation of S-containing compounds. 2- An anchoring layer and a stabilizing layer with an average sulfur oxidation state m2 satisfying -2 < m < 0 are used to prepare positive electrode active materials.

[0110] Example 2

[0111] Example 2 is basically the same as Example 1, except that 10.5g of sodium sulfide is added in step (2) of Example 2.

[0112] Example 3

[0113] Example 3 is basically the same as Example 2, the main difference being that in step (1) of Example 3, the precursor raw material is Ni. 0.7 Co 0.3(OH)2, purchased from Aladdin Reagent, with a particle size of 2~15μm.

[0114] Comparative Example 1

[0115] Comparative Example 1 is basically the same as Example 1, the main difference being that Comparative Example 1 only includes step (1), the specific steps of which are as follows:

[0116] The precursor material (Ni) 0.6 Co 0.4 (OH)₂ (purchased from Aladdin Reagent, particle size 2~15μm) was mixed with lithium hydroxide to prepare a mixture, in which the molar ratio of Li to (Ni+Co) in the mixture was 1.05:1; the mixture was heated in a box furnace under oxygen atmosphere at 950℃ for 15 h, and then pulverized by rollers (upper gap 15cm, lower gap 5cm) to obtain LiN i0.6 Co 0.4 O2 matrix.

[0117] Comparative Example 2

[0118] Comparative Example 2 provides a cathode material (LiNi) coated using a conventional dry method. 0.6 Co 0.4 O2@Al2O3), the specific steps are as follows:

[0119] The matrix was prepared in exactly the same manner as in Example 1. The matrix (2500 g) was mixed with nano-alumina (10 g) and sintered at 450 °C for 8 h in an air atmosphere in a box furnace.

[0120] Comparative Example 3

[0121] Comparative Example 3 provides a cathode material (LiNi) coated using a conventional dry method. 0.6 Co 0.4 O2@TiO2), the specific steps are as follows:

[0122] The matrix was prepared in exactly the same manner as in Example 1. The matrix (2500 g) was mixed with nano-titanium dioxide (10 g) and sintered at 450 °C for 8 h in an air atmosphere in a box furnace.

[0123] Comparative Example 4

[0124] Comparative Example 4 is basically the same as Example 1, except that Comparative Example 4 only includes steps (1) and (2), and the product prepared is a sulfide Li2S pre-coated lithium transition metal oxide modified material.

[0125] X-ray photoelectron spectroscopy (XPS) was performed using an AXIS Supra X-ray photoelectron spectrometer to study the surface element types and chemical environment of the positive electrode active materials in the examples and comparative examples. The positive electrode active materials prepared in Examples 1-3 and Comparative Examples 1-4 were assembled into coin cells, wherein the ratio of positive electrode active material to conductive carbon black was 90:10 wt%, the solvent was NMP, and the cell electrode surface density was 1.2 mg / cm³. 2 At 2.8-4.4V and 45℃, after one charge-discharge cycle at 0.1C / 0.1C rate, and then 50 cycles at 1C / 1C rate at 45℃, the battery was disassembled, the positive electrode was cleaned with DMC, dried, and the positive electrode active material powder was scraped off for surface metal element valence state analysis. First, the full spectrum peaks from 0 to 1200 eV were scanned, and then the fine peaks of Ni were tested. Ni was obtained through peak separation. 2+ and Ni 3+ The proportions are shown in Table 1.

[0126] Table 1

[0127]

[0128] As can be seen from Table 1, the average oxidation state of Ni on the surface of the materials in Examples 1-3 is higher than that in Comparative Examples 1-4. This indicates that the surface stabilizing layer has a stabilizing effect on the active sites of Ni on the surface, increases the average oxidation state of Ni on the surface, inhibits the formation of divalent nickel compounds NiO in the surface rock salt phase, and further avoids the reduction of the electrochemical performance of the material by inert NiO.

[0129] The positive electrode active materials prepared in Examples 1-3 and Comparative Examples 1-4 were assembled into coin cells, wherein the ratio of positive electrode active material to conductive carbon black was 90:10wt%, the solvent was NMP, and the electrode surface density was 1.2 mg / cm³. 2 When the battery was fully charged (4.4V), it was stored at 60℃ for 30 days and 60 days respectively. The battery was then disassembled, the positive electrode was cleaned with DMC, dried, and the active material layer of the positive electrode was scraped off. This layer was then dissolved in aqua regia by heating for 15-30 minutes. The solution was subjected to ICP testing to determine the dissolution of active transition metal elements such as Ni, Co, and Mn. The dissolution of Ni and Co elements in the electrolyte was also tested. The results are shown in Table 2 and... Figure 3 As shown.

[0130] Table 2

[0131]

[0132] As can be seen from Table 2, the amount of active transition metal elements Ni and Co leached from the battery made of the material in this embodiment of the application after long-term storage is significantly lower than that in the comparative example. This indicates that the material in this embodiment of the application is resistant to HF corrosion. Due to the presence of the coating layer, an effective and stable interface layer can be formed, which isolates and inhibits the corrosion of the material by HF, reduces the interface reaction of the electrode / electrolyte, and reduces the amount of transition metal leached.

[0133] The positive electrode active materials prepared in each embodiment and comparative example were assembled into coin cells, wherein the ratio of positive electrode active material to conductive carbon black was 90:10wt%, the solvent was NMP, and the cell electrode surface density was 1.2 mg / cm³. 2 The coin cells were cycled 50 times at a voltage of 2.8V-4.45V and a temperature of 45℃ at a rate of 0.1C / 0.1C. After cycling, the cells were disassembled, the positive electrode plates were cleaned with DMC, and after drying, the positive electrode active material powder and the positive electrode active materials prepared in each example and comparative example were scraped off and placed in the sample stage of an XRD testing instrument (model Bruker D8). A scan rate of 1° / min and a scan angle range of 10° to 80° were used. The XRD data were processed using GSAS refinement and Pawley full-spectrum fitting. The XRD comparison results are shown below. Figure 2 As shown in Table 3.

[0134] Table 3

[0135]

[0136] Depend on Figure 2 As can be seen, no impurity peaks appeared in the samples of the examples after 50 cycles, indicating that the coated material did not change the crystal structure of the positive electrode active material under extreme cycling conditions and could maintain the structural stability of the material. In addition, as can be seen from Table 3, the 003 / 104 peak of the examples is significantly higher than that of the comparative examples, and has a lower Li / Ni mixed site occupancy, indicating that the positive electrode active materials of Examples 1 to 3 have better stability of the layered structure.

[0137] The change rate of the interlayer spacing after 50 cycles was calculated as ΔH = [H2 (50 cycles) - H1 (0 cycles)] / H1 (0 cycles), where H2 is the interlayer distance between the transition metal and O layers in the lithium composite transition metal oxide surface layer after 50 cycles, and H1 is the interlayer distance between the transition metal and O layers in the lithium composite transition metal oxide surface layer before charging. The change rate of the interlayer spacing after 50 cycles is shown in Table 3. When the change rate of the interlayer spacing after 50 cycles is not higher than 10%, it is considered that the material has good interfacial stability. When the change rate of the interlayer spacing is greater than 10%, it can be considered that the surface structure of the material has undergone serious structural distortion. The main reason for the surface structure distortion is that the interface of the material is corroded by the electrolyte or HF generated by the electrode / interface reaction, resulting in the formation of rock salt phase, etc. The results show that the ΔH value of the embodiment is within 10% and significantly lower than that of the comparative example, while the change rate of the transition metal interlayer spacing of the comparative example is higher than 10%. This indicates that the positive electrode active material prepared in the embodiment has better surface structural stability.

[0138] The materials prepared in the examples and comparative examples were subjected to 45°C cycling and DCR performance tests, respectively. The test methods are as follows: appropriate amounts of the materials prepared in the examples and comparative examples were weighed and assembled into coin cells, wherein the electrode material: conductive carbon black = 90:10 (wt%), the solvent was NMP, and the cell electrode surface density was 1.2 mg / cm³. 2 At 2.8-4.4V and 45℃, the battery underwent one charge-discharge cycle at a rate of 0.1C / 0.1C, followed by a 50-cycle cycle at 45℃ and a rate of 1C / 1C. The material's DCR growth was calculated as follows: At the start of each battery cycle, the battery was discharged at 1C for 10 seconds, then allowed to rest before normal charge-discharge. After the 50th cycle, the material's DCR = (discharge voltage drop at the start of the 50th cycle) / discharge current. The DCR growth after 50 cycles = (DCR after the 50th cycle - DCR after the 1st cycle) / DCR after the 1st cycle. The test results are as follows: Figure 4 As shown in Table 4.

[0139] Table 4

[0140]

[0141] As shown in Table 4, compared with Comparative Example 1, Comparative Examples 2 and 3 exhibit significant improvements in capacity and retention, and a significant decrease in DCR, indicating that the traditional solid-phase coating method can indeed improve the material interface and enhance the electrochemical performance of the material. Data from Examples 1-3 show that the batteries prepared from the materials in this application exhibit a further increase in charge / discharge capacity of ~2 mAh / g compared to Comparative Examples 2-4, while the DCR growth after 50 cycles further decreases by ~20%. This demonstrates that the coating layer prepared in this application can effectively stabilize interfacial active transition metal elements, significantly improving material capacity, cycle performance, and DCR growth.

[0142] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0143] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. A positive electrode active material, characterized in that, The system comprises lithium transition metal oxide particles and a coating layer disposed on the surface of the lithium transition metal oxide particles. The coating layer includes an anchoring layer and a stabilizing layer stacked on top of each other. The anchoring layer is closer to the surface of the lithium transition metal oxide particles than the stabilizing layer. The chemical formula of the lithium transition metal oxide particles is Li. 1+x Ni y R z M 1-y-z O u Wherein, -0.2≤x≤0.2, 0.3≤y≤0.8, 0≤z≤0.7, y+z≤1, 1.8≤u≤2.2; R includes one or more of Co or Mn; M includes one or more of Al, Zr, Mg, Ti, W, B, Y, Sr, Nb and Mo. The anchoring layer and the stabilizing layer both contain sulfur, with the average valence of the sulfur in the stabilizing layer being greater than that in the anchoring layer. The anchoring layer is formed by inducing Ni, R, or M in the lithium transition metal oxide particles through sulfide Q₂S, where Q includes Na. + Li + and NH4 + One or more of the following; the anchoring layer satisfies m1=-2; where m1 is the average valence of sulfur contained in the anchoring layer; the stabilizing layer is formed by inducing the formation of the sulfide Q2S by elemental sulfur, such that the stabilizing layer satisfies: -2<m2<0; where m2 is the average valence of sulfur contained in the stabilizing layer; The anchoring layer is used to anchor the active elements in the lithium transition metal oxide particles, and the total dissolution amount of transition metal in the lithium transition metal oxide particles with the coating layer is ≤4000ppm.

2. The positive electrode active material according to claim 1, characterized in that, The positive electrode active material has one or more of the following characteristics: (1) The particle size of lithium transition metal oxide particles is 2μm~15μm; (2) The thickness of the anchoring layer is 5nm~50nm; (3) The thickness of the stabilizing layer is 5nm~50nm.

3. The positive electrode active material according to claim 1 or 2, characterized in that, After the positive electrode active material is assembled into a coin cell and cycled 50 times, the positive electrode active material has one or more of the following characteristics: (1) In the X-ray diffraction test, the ratio of the 003 peak to the 104 peak of the positive electrode active material is ≥1.45; (2) In the X-ray diffraction test for refinement, the change rate of the interlayer distance between the transition metal and oxygen in the positive electrode active material is ΔH≤10%; where ΔH=(H2-H1) / H1, H2 represents the interlayer distance between the transition metal and oxygen in the positive electrode active material after 50 cycles; H1 represents the interlayer distance between the transition metal and oxygen in the positive electrode active material when there are 0 cycles.

4. A method for preparing the positive electrode active material according to any one of claims 1 to 3, characterized in that, Includes the following steps: Lithium transition metal oxide particles and sulfide Q2S were mixed and calcined at 200℃~700℃ to prepare sulfide Q2S pre-coated lithium transition metal oxide modified materials; Q includes Na. + Li + and NH4 + One or more of the following; Sol A is prepared by mixing the sulfide Q2S pre-coated lithium transition metal oxide modified material and dispersant in carbon disulfide solvent; Solution B is prepared by dissolving elemental sulfur in carbon disulfide solvent; The solution B is introduced into sol A for deposition, and after solid-liquid separation, it is sintered at a temperature of 200℃~800℃ to prepare the positive electrode active material.

5. The method for preparing the positive electrode active material according to claim 4, characterized in that, The preparation method has one or more of the following characteristics: (1) The mass ratio of the lithium transition metal oxide particles to the sulfide Q2S is 1:(0.001~0.1); (2) The solid content of the sol A is 5%~50%; (3) The concentration of elemental sulfur in solution B is 0.001 mol / L to 1 mol / L; (4) The mass ratio of the pre-coated lithium transition metal oxide modified material to the elemental sulfur is 1:(0.001~0.1). (5) The rate at which the solution B is introduced into the sol A is 0.4 g / min to 0.6 g / min.

6. The method for preparing the positive electrode active material according to claim 4 or 5, characterized in that, The preparation steps of the lithium transition metal oxide particles include: A mixture is prepared by mixing the precursor with a lithium source; The mixture was sintered at a temperature of 400℃~1000℃ to prepare the lithium transition metal oxide particles; The precursor has the chemical formula Ni y1 R z1 M 1-y1-z1 O u1 Wherein, 0.3≤y1≤0.8, 0≤z1≤0.7, y1+z1≤1, 1.8≤u1≤2.2; R includes one or more of Co or Mn; M includes one or more of Al, Zr, Mg, Ti, W, Y, Sr, Nb and Mo.

7. A positive electrode, characterized in that, It includes a positive current collector and a positive active material layer stacked on the surface of the positive current collector, wherein the positive active material layer includes the positive active material according to any one of claims 1 to 3 or the positive active material prepared by the preparation method according to any one of claims 4 to 6.

8. A lithium-ion battery, characterized in that, include: The positive electrode as described in claim 7; The negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector; Diaphragm and electrolyte.

Citation Information

Patent Citations

  • Sulfide-coated positive electrode material, preparation method thereof and lithium ion battery

    CN112447948A

  • Method for preparing positive electrode material through coating modification of metal sulfide

    CN116799153A